The inheritance of a -Daughter in the Iraqi Personal Status Law - Rahim, Bakhtiar Sediq (Journal of Legal and Political Studies, 2016)
Take matters related to personal status in Islamic societies a high position in the hearts and conscience of everyone of its members, and is seeking individuals and families on the sponsorship and apply the rule of personal status, even if they become disregard in other worship services issues, legacy is a part of these issues, Because of in Islamic jurisprudence, as well as the legal legislator of interest which suits it, but we find sometimes that the legislator, under the effects of multiple subjects deviate from the agreed opinion a way that not be a desirable times, and rejected other times .As an example on that stipulated by the Iraqi legislature when his statement to the legacy of the girl the negative in terms of its share and strength in blocking form in which it was requiring him analytical pause, to see rooting the jurisprudence to the stipulated, and the statement of stops of defect in it for non-conformity with the jurisprudence, and then a statement ways to address that is derived from religious texts legal treatment, and in conformity with the religion doctrine of the people and social conditions prevailing.
Keywords: personal status; Islamic jurisprudence; legal treatment; Legislator